PENGARUH MODEL REACT TERHADAP BERPIKIR KRITIS PENDIDIKAN AGAMA ISLAM SMA IT AL AMRI - Rofiqo; Agustin , Maulid (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2024)
This research is a quantitative study which aims to evaluate the effect of implementing the REACT Model on students' critical thinking abilities at AL-AMRI IT High School, Leces Village, Leces District, Probolinggo Regency. The data obtained was processed using descriptive statistics and the SPSS application. The results of the analysis show that there is a significant influence between the application of the REACT Model (variable X) on critical thinking skills (variable Y) at SMA IT AL-AMRI. The calculated t value is 13.795 with a significance of 0.000 (less than 0.05), indicating that the REACT Model has a significant influence on students' critical thinking abilities. The correlation analysis value (R) is 0.302, and the coefficient of determination (R square) is 0.091, indicating that 18.4% of the variation in students' explicit reasoning skills can be understood using the Response Model, while other elements contribute 81%. 6%. Based on exam results, it tends to be argued that schools play an important role in developing students' true capacities. Implementing learning techniques such as the Response Model can be an effective solution in further developing students' critical thinking abilities. This is important considering the difficulties in the world of education, especially related to problems with educational experiences and students' lack of critical thinking skills. Furthermore, this exam provides a significant commitment to the advancement of more successful learning techniques under instructive conditions.